INDUSTRIAL AND TECHNOLOGICAL STRUCTURALS OF THE UKRAINE ECONOMY - Anna A. Smaglyuk (Статистика и экономика, 2016)
The importance of total factor productivity for improving national competitiveness is presented based on the calculations. The trends of industrial and technological structural changes are analysed. The methods of overcoming existing structural problems of the Ukraine economy are given.